Microbiologic profile of flexible endoscope disinfection in two Brazilian hospitals - Machado, Alexandre Paulo [UNIFESP] (2006)
BACKGROUD: Endoscopes are routinely used in hospitals and clinics of the world and they can be potential sources of cross-infection when the decontamination process is unsuitable AIM: The routines of flexible endoscope (bronchoscopes, esophagogastroduodenoscopes and colonoscopes) disinfection procedures used in two Brazilian university hospitals were evaluated during a 3-year period METHODS: Aleatory samples from internal channels of endoscopes were collected after patient examination and after cleaning/disinfection procedures RESULTS: A contamination >3 log10 was achieved in samples recovered from endoscopes after patient examination. These samples yielded gram-negative bacilli (n = 142: 56%), gram-positive cocci (n = 43: 17%), yeast cells (n = 43: 17%), and gram-positive bacilli (n = 26: 10%). Approximately, 72 out of 149 samples (48.32%) collected after undergoing the cleaning and disinfection procedures disclosed gram-negative bacilli (n = 55: 61%), gram-positive cocci (n = 21: 23%), gram-positive bacilli (n = 8: 9%) and yeast cells (n = 6: 7%). Esophagogastroduodenoscopes and colonoscopes were the most frequently contaminated devices. Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli, Enterobacter spp, Serratia marcescens, Proteus mirabilis, Citrobacter freundii, Staphylococcus aureus, Staphylococcus coagulase negative, Micrococcus luteus, Candida albicans, C. tropicalis, C. glabrata, C. guilliermondii, Bacillus spp and Corynebacterium spp were predominantly identified CONCLUSION: Inappropriate cleaning and low times of disinfection were respectively the major factors associated with the presence of microorganisms in colonoscopes and esophagogastroduodenoscopes. By analyzing the identified germs, hospital disinfection was considered of either intermediate or poor level. After this investigation, both university centers improved their previous protocols for disinfection and conditions for reprocessing endoscopes.